Association between antioxidant status and MnSOD Ala-9Val polymorphism in trained male athletes (rugby players) and sedentary male students controlled for antioxidant intake - Seele, Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.